Pharmacokinetics of zonisamide after oral single dosing and multiple‐dose escalation administration in domestic chickens (Gallus gallus). Issue 5 (18th May 2021) - de Matos, Ricardo; Noonan, Brendan P.; Schaefer, Deanna M.W.; Morrisey, James; Dewey, Curtis; Buckles, Elizabeth L.; Boothe, Dawn
Abstract: Background: There are few effective drugs for treatment of seizures in avian species. Objectives: To investigate the pharmacokinetics and safety of zonisamide in chickens. Methods: Phase 1: chickens ( n = 4) received a single oral dose of zonisamide at 20 mg/kg. Blood samples were collected intermittently for 36 hr after dosing. Phase 2: chickens ( n = 8) received zonisamide in a dose escalation protocol (20, 30, 60 and 80 mg/kg orally every 12 hr). The dose was increased weekly, and peak and trough blood samples were collected on Days 1, 3, and 7 each week. Two birds were randomly euthanized at the end of each week. Plasma zonisamide concentrations were analysed using a commercial immunoassay. Drug concentration vs. time data were subjected to non‐compartmental pharmacokinetic analysis. Results: For Phase 1, peak plasma zonisamide (Cmax ) was 15 ± 3 µg/ml at 2 ± 1 hr (Tmax ). The disappearance half‐life was 6.5 ± 1 hr. Mean plasma concentrations remained within the (human) therapeutic range (10–40 µg/ml) for 6 hr. For Phase 2 of the study, plasma concentrations of zonisamide remained within or close to the recommended mammalian therapeutic range for birds in the 20 and 30 mg/kg dose. Area under the curve (AUC) and Cmax were dose dependent. Two birds developed immune‐mediated haemolytic anaemia. Conclusions: Zonisamide appears to be a viable drug for use in chickens at a dose of 20 mg/kg orally every 12 hr. Abstract : The pharmacokinetics and safety of zonisamide were investigated in chickens in single and repeated dose trials. Zonisamide appears to be a viable drug for use in chickens at a dose of 20mg/kg orally every 12 hr.